Zakat Model For Countering The Adverse Impact Of Covid-19 Pandemic On Individuals In Bauchi State Nigeria - Adamu Abubakar Muhammad; Ibrahim Dahiru Idriss (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition